Comparison of R(2)* Correction Methods for Accurate Fat Quantification in Fatty Liver - Horng, Debra E. (2012)
PURPOSE: To compare the performance of fat fraction quantification using single- [Formula: see text] and dual- [Formula: see text] correction methods in patients with fatty liver, using MR spectroscopy (MRS) as the reference standard. MATERIALS AND METHODS: From a group of 97 patients, 32 patients with hepatic fat fraction greater than 5%, as measured by MRS, were identified. In these patients, chemical shift encoded fat-water imaging was performed, covering the entire liver in a single breath-hold. Fat fraction was measured from the imaging data by post-processing using 6 different models: single- and dual- [Formula: see text] correction, each performed with complex fitting, magnitude fitting and mixed magnitude/complex fitting to compare the effects of phase error correction. Fat fraction measurements were compared to co-registered spectroscopy measurements using linear regression. RESULTS: Linear regression demonstrated higher agreement with MRS using single- [Formula: see text] correction compared with dual- [Formula: see text] correction. Among single- [Formula: see text] models, all 3 fittings methods performed similarly well (slope = 1.0 ± 0.06, r(2)=0.89–0.91). CONCLUSION: Single- [Formula: see text] modeling is more accurate than dual- [Formula: see text] modeling for hepatic fat quantification in patients, even in those with high hepatic fat concentrations.